Characterization of Si0.25Ge0.75 -FinFET as a Temperature Nano Sensor - YOUSIF ATALLA; Mohamad Hafiz Mamat; Yasir Hasyim (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
This study addresses the impact of thermal sensitivity on the performance of FinFET transistors, with a focus on the role of different channel lengths in enhancing electrical performance.  As semiconductor technology advances, understanding the effects of temperature on electronic devices becomes essential to ensure their stability in various applications. Semiconductor manufacturing has stuck to Moore's law, which requires reducing the size of transistors to magnify integration and reduce costs, but biosensors with classic planar transistors are receptive to the effects of short channels, leading to increased power wastage and minimizing sensitivity. FinFET structure shows higher-level gate control, increased repression of short-channel issues. The research uses simulation techniques to study the current-voltage (I-V) behavior in a FinFET structure that relies on Si0.25Ge0.75 as the channel semiconductor material.  The effect of different temperatures (275, 300, 325, and 350 °K) with channel lengths of 10, 20, and 30 nm is analyzed, focusing on the change in current (∆I) within the operating voltage range of 0 to 1 V (VDD).  The results reveal that thermal sensitivity increases with the reduction of channel length, especially between 10 and 20 nanometers, where the optimal length is found to be 20 nm, due to its balance between low threshold voltage and reduced drain-induced barrier lowering (DIBL), while maintaining stable performance within the studied temperature range.  The study also showed that the device operates efficiently at a drain voltage (Vd) of 0.9 volts, ensuring stable performance in the range of 325-350 Kelvin.  These results highlight the importance of adjusting design parameters to improve the thermal response of FinFETs, contributing to the development of semiconductors and their applications in nanotechnology and advanced electronics.